Understanding poverty - Banerjee, Abhijit; Benabou, Roland; Mookherjee, Dilip (Oxford Oxford University Press, 2006)
"Understanding poverty and what to do about it, is perhaps the central concern of all of economics. Yet the lay public almost never gets to hear what leading professional economists have to say about it. This volume brings together twenty-eight essays by some of the world leaders in the field, who were invited to tell the lay reader about the most important things they have learnt from their research that relate to poverty. The essays cover a wide array of topics: the first essay is about how poverty gets measured. The next section is about the causes of poverty and its persistence, and the ideas range from the impact of colonialism and globalization to the problems of "excessive" population growth, corruption and ethnic conflict. The next section is about policy: how should we fight poverty? The essays discuss how to get drug companies to produce more vaccines for the diseases of the poor, what we should and should not expect from micro-credit, what we should do about child labor, how to design welfare policies that work better and a host of other topics. The final section is about where the puzzles lie: what are the most important anomalies, the big gaps in the way economists think about poverty? The essays talk about the puzzling reluctance of Kenyan farmers to fertilizers, the enduring power of social relationships in economic transactions in developing countries and the need to understand where aspirations come from, and much else. Every essay is written with the aim of presenting the latest and the most sophisticated in economics without any recourse to jargon or technical language."--Publisher description.
Introduction and overview / Abhijit Vinayak Banerjee ... [et al.] -- Measuring poverty / Angus Deaton -- Part I. The causes of poverty -- Understanding prosperity and poverty : geography, institutions, and the reversal of fortune / Daron Acemoglu ... [et al.] -- Colonialism, inequality, and long-run paths of development / Stanley L. Engerman, Kenneth L. Sokoloff -- The Kuznets curve : yesterday and tomorrow / Thomas Piketty -- New growth approach to poverty alleviation / Philippe Aghion, Beatriz Armendáriz de Aghion -- Globalization and all that / Abhijit Vinayak Banerjee -- The global economy and the poor / Pranab Bardhan -- The role of agriculture in development / Mukesh Eswaran, Ashok Kotwal -- Fertility and income / T. Paul Schultz -- Fertility in developing countries / Mukesh Eswaran -- Corruption and development / Jean-Jacques Laffont -- Ethnic diversity and poverty reduction / Edward Miguel -- Part II. How should we go about fighting poverty? -- Redistribution toward low incomes in richer countries / Emmanuel Saez -- Transfers and safety nets in poor countries: revisiting the trade-offs and policy options / Martin Ravallion -- Poverty persistence and design of antipoverty policies / Dilip Mookherjee -- Child labor / Christopher Udry -- Policy dilemmas for controlling child labor / Kaushik Basu -- The primacy of education / Anne Case -- Public goods and economic development / Timothy Besley, Maitreesh Ghatak -- Intellectual property and health in developing countries / Jean Tirole -- Public policies to stimulate development of vaccines for neglected diseases / Michael Kremer -- Microinsurance : the next revolution? / Jonathan Morduch -- Credit, intermediation, and overty reduction / Robert M. Townsend -- Part III. New ways of thinking about poverty -- Poor but rational? / Esther Duflo -- Better choices to reduce poverty / Sendhil Mullainathan -- Nonmarket institutions / Kaivan Munshi -- Racial stigma: toward a new paradigm for discrimination theory / Glenn C. Loury -- Aspirations, poverty, and economic change / Debraj Ray.
Keywords: Poverty; Poor